A boy with torticollis caused by a high cervical spine anomaly - Choi, J. Y.; Park, E. S. (Osteologie, 2015)
The structural abnormalities of the cervical spine can be a cause of torticollis. Congenital cervical spine anomalies are a rare cause of torticollis in young children. Because a high cervical anomaly confers increased risk of instability and spinal cord encroachment, early detection of the anomaly is essential to avoid potentially harmful physical therapy and to provide an opportunity to initiate an adequate therapeutic plan. Here we report an interesting case of torticollis. A 5-year-old boy presented to our clinic for further assessment of torticollis. Radiologic examination revealed an extra hemi-vertebra on the right side between C1 and C2 and also a C4 butterfly vertebra with concurrent rib anomaly. In this report, we describe his clinical manifestations with a brief review of cervical spine anomalies resulting in torticollis reported in the literature.
Keywords: Torticollis; cervical spine anomaly